Respon Eksplan Biji Gaharu (Aquilaria malaccensis Lamk.) terhadap Pemberian IAA secara In Vitro - Melva Sari Gultom; Nelly Anna; Edy Batara Mulya Siregar (Peronema Forestry Science Journal, 2012)
Agarwood (Gaharu) is an important non-timber forest products and has high economic value. The agarwood is the final product obtained from species A.malaccensis Lamk as raw material for the pharmaceitical and cosmetic industries. Increasing of the gaharu collection and international market circulation have resulted in the decline of the gaharu. The presence of gaharu in nature endangered triggers to do multiplication  aloes one with tissue culture technique. This research aims to determine the response of seed explants A.malaccensis and determine the concentration of the best growth regulator. This research used a Complete Random Design (RAL) with Growth  Regulator IAA in any concentrates with agarwood seed explants. The results showed that giving of IAA growth regulator that responds to the growing sprouts. Treatment concentration of IAA significant to the time sprouts appear but not significant on the appearance of sprouts, number of leaves and sprouts length. Emerging sprouts fastest time occurred in the treatment of 6 ppm IAA 9 days after planting. Keyword: Agarwood, Tissue Culture, Growth Regulator